Essays in semantics and pragmatics : in honor of Charles J. Fillmore - Fillmore, Charles J.; Shibatani, Masayoshi; Thompson, Sandra A. (Pragmatics & beyond, 1995)
This volume reflects the influence of Chuck Fillmore's ground-breaking work in the fields of semantics and pragmatics. The papers in the volume pay tribute to his pioneering research into the deepest realms of the nature of 'meaning'.